Improvement of Casting Technology by Using of Exothermic Feeder Head and Simulation the Solidification Alloy - Beatrice TUDOR (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2012)
This paper presents a simulation program use of feeders exothermic and insulating plates. High quality casting is considerably improved by using solidification simulation flow and cast.